Sanitary and hygienic conditions for effective sports activities of players - Kogan O.S.; Yamileva R.M.; Greb A.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to give a detailed sanitary and hygienic description of the conditions of professional sports activities of team sports athletes and to prove that overload and overtraining of the body cannot but have a negative impact on the health of athletes, especially among athletes with high professional experience. Methods and structure of the study. The microclimate of indoor sports facilities, temperature conditions, lighting, dust, and microbial contamination of training premises were studied. When analyzing the state of adaptation of the athletes’ body, the indicators of cardiointervalography (CIG) were determined using the method of R.M. Baevsky in terms of the magnitude of the mode amplitude (AMo) and voltage index (VI). The state of health and circulatory system of gaming athletes was also analyzed based on the prevalence of chronic non-infectious diseases and ECG. Results and conclusions. The results obtained indicated a significant decrease in the level of adaptation of the body and a lower level of health among trained athletes-players compared to the control group. These conclusions necessitate a government solution to many medical and legal problems regarding compliance with labor rights and guarantees, decent social security and full medical rehabilitation of athletes, both those who continue their sports career and those who have completed it, when they receive sports injuries and injuries.